Direct Monitoring of Verapamil Level in Exhaled Breath Condensate Samples - Fariba Pourkarim; Elaheh Rahimpour; Maryam Khoubnasabjafari; Vahid Jouyban-Gharamaleki; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2019)
Background: In this research, an enhanced fluorimetric assay was developed for the direct monitoring of verapamil in exhaled breath condensate (EBC). The method is based on a binding-induced rigidity inside the sodium dodecyl sulfate (SDS) micelle which eliminate collisional quenching and vibrational modes responsible for non-radiative decay. This process produces an enhancement in the emission intensity of verapamil. Methods: Fluorescence intensity measurements were made at 15 ˚C on a FP-750 spectroﬂuorometer with maximum excitation and emission wavelengths of 280 nm and 310 nm, respectively. The important parameters influencing the analytical signal in experimental steps were investigated and optimized. The method was validated with considering of the linearity, recovery and limit of detection. Results: Under the optimized experimental conditions, the calibration graph was linear in the range of 0.02 − 12.0 µg.mL−1 of verapamil with a detection limit of 0.008 µg.mL-1. Conclusion: The proposed method was found to be suitable and accurate for the determination of verapamil and the validated method was successfully used for analysis of verapamil in EBC of patients receiving verapamil with the satisfactory results.